2009
DOI: 10.1063/1.3108539
|View full text |Cite
|
Sign up to set email alerts
|

Optical dielectric constant inhomogeneity along the growth axis in ZnO-based transparent electrodes deposited on glass substrates

Abstract: Simple optical measurements using a conventional spectrometer have revealed that in heavily doped ZnO films deposited on glass, the optical dielectric constant is inhomogeneous along the growth axis. Analyses based on Drude’s model have suggested that the origin of this inhomogeneity is the shorter carrier scattering time τc in the portion in contact with the glass substrate, while τc in the major portion of the films has been estimated to be as long as 1×10−14 s at infrared frequencies. This may imply that if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Crystallinity is poorest at the beginning of growth, but it gradually improves as the growth front departs from the interface. In fact, Ikegami et al 3 experimentally found that the scattering lifetime of carriers in the interface region is shorter than that in the upper region. The crucial point to improve the conductive properties is minimizing the thickness of the transitional region, where crystallinity varies from amorphous to highly c-plane-oriented ZnO crystallites.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallinity is poorest at the beginning of growth, but it gradually improves as the growth front departs from the interface. In fact, Ikegami et al 3 experimentally found that the scattering lifetime of carriers in the interface region is shorter than that in the upper region. The crucial point to improve the conductive properties is minimizing the thickness of the transitional region, where crystallinity varies from amorphous to highly c-plane-oriented ZnO crystallites.…”
Section: Introductionmentioning
confidence: 99%
“…An aluminum-doped zinc oxide (hereafter abbreviated as AZO) films was deposited onto 10 × 10 cm glass plates by rf magnetron sputtering, as in the case of the previous works [4]. Its thickness and conductivity, which were measured by a surface profiler and the van der Pauw method, were 518 nm and 2.67 S/cm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Its thickness and conductivity, which were measured by a surface profiler and the van der Pauw method, were 518 nm and 2.67 S/cm, respectively. Its plasma frequency was estimated at 2.7 × 10 15 s -1 (corresponding to a wavelength of 700 nm) based on the optical measurements in the previous study [4]. The AZO substrates were prepared by cutting the AZO-coated glass into pieces with the dimensions of 3.8 × 1.3 cm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc oxide (ZnO), is one of the most important multifunctional n-type II-VI compound semiconductors, with a direct wide bandgap (3.37 eV), high exciton binding energy (60 meV) at room temperature and superior thermal stability [2]. As an important semiconductor material, ZnO has attracted considerable attentions due to its unique piezoelectric [3], pyroelectric [4], catalytic and photocatalytic properties [5], and its potential applications in preparing solar cells [6], gas sensors [7], UV photodiodes [8], piezoelectric devices [9], transparent electrodes [10] and optoelectric devices [11]. Moreover, ZnO is also nontoxic, bio-safe, and possibly biocompatible and hereby can be directly used for biomedical applications without additional coating [12].…”
Section: Introductionmentioning
confidence: 99%